Palynostratigraphical - Walid A. Makled; Abdel Hakam A. Baioumi; Rehab A. Saleh (Egyptian Journal of Petroleum)
The Kharita and Bahariya formations are of great importance for Egyptian economy. They are the target of the oil and gas exploration in the Egyptian Western Desert. The present study investigated the palynostratigraphy, palynofacies and spore coloration of samples from these two formations in Negelah-1 Borehole. The investigations were used to evaluate their thermal maturity and potentiality to generate the hydrocarbons. The identified palynozones are Afropollis jardinus Acme Zone (late Albian–early Cenomanian) and Araucariacites australis Acme Zone (middle Albian). The first zone is differentiated into two subzones, which are Elaterosporites klaszii Interval Subzone and Cretacaeiporites densimurus Interval Subzone. The palynofacies analysis revealed that the Kharita Formation was deposited in proximal near shore marine environment under oxic conditions. Whereas the lower part of the Bahariya Formation was initially deposited in proximal near shore dysoxic marine conditions and the environment of deposition getting more distal to inner shelf dysoxic to anoxic marine conditions in the younger upper part. The samples from both formations include gas prone type III and IV. The spore color observations indicated that the samples from both formations are immature to yield gas and are not effective hydrocarbon source.